THEORETICAL BASIS OF FORMING COMPETENCE IN FUTURE PHYSICAL EDUCATION TEACHERS - Toshpulatova Aziza Toyirovna (Bright Mind Publishing, 2025)
This article is devoted to the topic of forming general cultural competencies of future physical education teachers, and provides information on competence, types of competence, competency-based approach, basic competence, general cultural competence. This article examines the concept of competence, its importance and what theoretical foundations exist in the training of future teachers.
Keywords: Competence, types of competence, competency-based approach, basic competence.